Modulating D-Band Center of SrTiO3 by Co Doping for Boosted Peroxymonosulfate (PMS) Activation Under Visible Light - Kaining Sun; Xinyi Yang; Fei Qi; Yingjie Liu; Lijing Wang; Bo Feng; Jiankang Yu; Guangbo Che (Molecules)
Peroxymonosulfate (PMS)-based advanced oxidation technology has emerged as an effective means for removing organic pollutants from water due to its strong oxidizing ability. However, enhancing the activation efficiency of PMS represents a key challenge at present. SrTiO3, a typical perovskite metal oxide, holds potential in the field of the photocatalytic degradation of pollutants, yet its application is limited by the wide bandgap and fast carrier recombination rates. This study optimized the photocatalytic performance of SrTiO3 by regulating its electronic structure and optical properties through cobalt (Co) doping. Experimental results (TRPL, TPV, UV–Vis DRS, ESR, etc.) and DFT calculations (GGA-PBE) demonstrated that Co doping shifted the d-band center of SrTiO3 upwards, optimized the adsorption energy of SO4−, enhanced the sunlight response range, and significantly improved carrier extraction efficiency. Under visible light irradiation, 2,4-dichlorophenol (2,4-DCP) could be effectively degraded within 60 min in a wide pH range. Through Fukui function calculation (B3LYP/6-31G*) and experimental characterization analysis (HPLC-MS and IC), the possible degradation pathways of 2,4-DCP and the mechanism for photocatalysis were investigated. The toxicity analysis (T.E.S.T) confirmed the reduced toxicity of the degradation products of 2,4-DCPs. This study provides a reference for the catalyst design and optimization strategy of PMS-based advanced oxidation technology.